Beauty isn’t everything: An agent-based model of imperfect food acceptance and market utility balance - Khaluf, Yara; de Hooge, Ilona E. (PLOS ONE, 2025)
Imperfect or suboptimal foods—cosmetically flawed yet nutritionally sound—are frequently discarded across the food supply chain, contributing significantly to global food waste. Although farmers, retailers, and consumers all influence this waste dynamic, existing research often treats their behaviors in isolation and fails to capture the evolving, systemic interplay among them. This study presents a novel agent-based model simulating interactions between farmers, retailers, and consumers in local produce markets to examine how preferences, stocking strategies, and marketing interventions shape market behavior over time. The model integrates behavioral mechanisms such as the mere-exposure effect and Prospect Theory to realistically represent consumer adaptation and decision-making. Through simulations across varying market configurations, we identify critical points in consumer behavior and market-wide utility. Our findings reveal that promoting imperfect foods can lead to substantial utility gains for both consumers and retailers—particularly when retailers stock high levels of imperfect products consistently over time. These results emerge from simulations showing that the mere-exposure effect drives consumer preference shifts even in the absence of marketing, enabling widespread acceptance under certain stocking strategies.